Avaliação da eficácia de crioprotetores permeantes e não permeantes no descongelamento rápido e lento do sêmen canino - Acipreste, Amanda Carla [UNESP]; Costa, Eduardo Paulino; Oliveira, Fabrício Albani; Costa, Sanely Lourenço; Silva, Talita Fernandes; Beretta, Daniel Cortes (Universidade Federal de Goiás, 2014)
The aim of this study was to evaluate the association between cryoprotectants little studied in Brazil such as dimethylformamide and trehalose amid thinner, using protocols of fast and slow defrosting. Three adult Labrador Retrievier male, healthy dogs, weekly submitted to one semen collection during five-weeks period, were used. The base diluent medium used in this study was tris-citrate added with 3% of dimethylformamide + 3% glycerol (D1), 3% dimethylformamide and trehalose (D2) and 4% glycerol (D3). At defrosting, half of the semen samples from each diluent medium was defrosted by rapid method in water-bath at 75 °C for seven minutes, followed by a new immersion at 37 °C for 1 minute. The other half of the samples was defrosted by slow method, in water-bath at 37 °C for 1 minute. The semen was evaluated for sperm progressive motility and vigor, besides membrane integrity. For this, the semen samples were submitted to either hyposmotic and membrane integrity tests of the plasmatic membrane and acrosome (fluorescence). The results indicated that the use of glycerol as cryoprotector in TRIS diluter provides greater efficacy in cryopreserving spermatozoa of the canine species, when compared to dimethylformamide associated with trehalose or glycerol.

O objetivo do trabalho foi avaliar o efeito da associação entre crioprotetores ainda pouco estudados no Brasil como a dimetilformamida e a trealose em meio diluidor, por meio de protocolos de descongelamento rápido e lento. Foram utilizados três cães machos, adultos, sadios da raça Labrador do Retrievier, que foram submetidos a uma coleta de sêmen semanal durante o período de cinco semanas. Os três meios diluentes utilizados neste estudo foram: (D1)-tris-citrato, acrescido de 3% de dimetilformamida + 3% de glicerol, (D2)-3% de dimetilformamida e de trealose e (D3)-4% de glicerol. No descongelamento, metade das amostras de cada meio diluente foi descongelada pelo método rápido, em banho-maria a 75ºC por sete segundos, seguido de nova imersão a 37 ºC por 1 minuto. A outra metade foi descongelada pelo método lento, em banho-maria à 37 ºC por 1 minuto. O sêmen foi avaliado quanto à motilidade progressiva, vigor espermáticos e integridade de membrana. Pra isso, as amostras foram submetidas aos testes hipo-osmótico e de integridade da membrana plasmática e do acrossoma (fluorescência). Os resultados indicam que o uso do glicerol como crioprotetor em diluidor TRIS proporciona maior eficácia na criopreservação dos espermatozoides da espécie canina, quando comparados com a dimetilformamida associada ao glicerol ou trealose.
Evaluating the effectiveness of permeating and non-permeating cryoprotectants in fast and slow defrosting of canine semen
Keywords: cão; criopreservação; dimetilformamida; glicerol; trealose; cryopreservation; dimethylformamide; dogs; glycerol; trehalose